2005
DOI: 10.1152/jn.00108.2005
|View full text |Cite
|
Sign up to set email alerts
|

Spike Timing in CA3 Pyramidal Cells During Behavior: Implications for Synaptic Transmission

Abstract: Spike timing is thought to be an important mechanism for transmitting information in the CNS. Recent studies have emphasized millisecond precision in spike timing to allow temporal summation of rapid synaptic signals. However, spike timing over slower time scales could also be important, through mechanisms including activity-dependent synaptic plasticity or temporal summation of slow postsynaptic potentials (PSPs) such as those mediated by kainate receptors. To determine the extent to which these slower mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 46 publications
6
42
0
Order By: Relevance
“…CA3 pyramidal neurons in vivo exhibit a range of firing patterns that can be interpreted as spanning from non-bursting to burst firing (Frerking et al, 2005). It is quite possible that the variability we observed in vitro contributes, at least in part, to that distribution.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…CA3 pyramidal neurons in vivo exhibit a range of firing patterns that can be interpreted as spanning from non-bursting to burst firing (Frerking et al, 2005). It is quite possible that the variability we observed in vitro contributes, at least in part, to that distribution.…”
Section: Discussionmentioning
confidence: 84%
“…During behavioral tasks the distribution of interspike intervals (ISI) of CA3 pyramidal neurons varies between cells (Frerking et al, 2005) with some neurons exhibiting bimodal distributions suggestive of at least two firing patterns; burst firing which comprises a fast ISI peak and regular, lower-frequency firing corresponding to a longer ISI peak distribution (Frerking et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, we have shown that the Syt2-expressing GABAergic synapses (Pang et al, 2006;Fox and Sanes, 2007;Kerr et al, 2008) established by neurons which typically fire action potentials at very high frequencies (ϳ200 Hz) (Ylinen et al, 1995;Csicsvari et al, 1999) are extremely dependent on CSP-␣ to maintain their functional and structural integrity over time, and therefore suffer from progressive degeneration on genetic removal of CSP-␣. In contrast, neighboring glutamatergic synapses from neurons that normally trigger action potentials at a lower frequency (ϳ1 Hz) (Csicsvari et al, 1999;Frerking et al, 2005) do not show signs of presynaptic degeneration in the absence of CSP-␣. These conclusions are based on the following findings: First, using immunofluorescence and electron microscopy, we have demonstrated progressive degeneration of GABAergic synapses both in vitro and in vivo (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…While it is the case that CA3 neurons discharge at very low frequencies on average (1–3 Hz; Csicsvari et al, 2000; Frerking et al, 2005), during the theta rhythm they typically fire bursts of 1–4 spikes (2.4 spikes per burst on average) with inter-spike-intervals (ISIs) ranging from 3 to 7 ms (Ranck, 1973; Tropp-Sneider et al, 2006; Mizuseki et al, 2009). This type of firing pattern is significant since, beyond the opportunity for classical temporal summation afforded by a train of inputs, glutamate binding kinetics lead NMDA conductances to increase substantially in response to brief trains compared to single stimuli (Mainen et al, 1999; Umemiya et al, 1999; Mcallister and Stevens, 2000; Oertner et al, 2002; Nimchinsky et al, 2004; Popescu et al, 2004; Polsky et al, 2009).…”
Section: Introductionmentioning
confidence: 99%